ACTUALIZING EQUALITY: A STRATEGY FOR WOMENS POLITICAL REPRESENTATION IN POLITICS IN THE 2024 ELECTIONS IN THE SPECIAL PROVINCE OF YOGYAKARTA - Martini, Ani; Lambelanova, Rossy; Murni, Hari Nur Cahya; Sentosa, Ilham (CosmoGov: Jurnal Ilmu Pemerintahan, 2024)
This study investigates the factors behind women’s low representation in the 2024 Legislative Elections in the Special Region of Yogyakarta (DIY) and formulates strategies to address the issue. Using qualitative methods and a descriptive approach, data was collected through interviews, observations, and documentation. The author conducted in-depth interviews with 11 informants from political institutions and election organizers in DIY. The study identifies five leading causes of low representation: lack of self-confidence and family support, cultural restrictions, insufficient political education, discrimination within political parties, and the high costs of political participation. Strategies were formulated using SOAR Analysis, yielding four approaches. The S-A Strategy emphasizes building political women’s empowerment centers, cultural campaigns, and strengthening collaboration networks. The O-A Strategy focuses on establishing political education programs, advocating for regulatory reforms, and electoral system improvements. The S-R Strategy highlights public awareness campaigns, collaboration optimization, and political education development. Lastly, the O-R Strategy emphasizes implementing political education programs, enhancing awareness through education, and fostering collaboration among institutions and organizations. These strategies aim to empower women, raise public awareness, and improve women’s political participation through targeted education, advocacy, and institutional collaborationgb777